The standard operating procedure of the DOE-JGI Metagenome Annotation Pipeline (MAP v.4). Issue 1 (December 2016) - Huntemann, Marcel; Ivanova, Natalia; Mavromatis, Konstantinos; Tripp, H.; Paez-Espino, David; Tennessen, Kristin; Palaniappan, Krishnaveni; Szeto, Ernest; Pillay, Manoj; Chen, I-Min; Pati, Amrita; Nielsen, Torben; et al.
Abstract The DOE-JGI Metagenome Annotation Pipeline (MAP v.4) performs structural and functional annotation for metagenomic sequences that are submitted to the Integrated Microbial Genomes with Microbiomes (IMG/M) system for comparative analysis. The pipeline runs on nucleotide sequences provided via the IMG submission site. Users must first define their analysis projects in GOLD and then submit the associated sequence datasets consisting of scaffolds/contigs with optional coverage information and/or unassembled reads in fasta and fastq file formats. The MAP processing consists of feature prediction including identification of protein-coding genes, non-coding RNAs and regulatory RNAs, as well as CRISPR elements. Structural annotation is followed by functional annotation including assignment of protein product names and connection to various protein family databases.